Visual comparison of software architectures. (April 2013) - Beck, Fabian; Diehl, Stephan
Reverse engineering methods produce different descriptions of software architectures. In this article we address the task of exploring and comparing these descriptions. We present a novel visualization technique to compare architectures consisting of a decomposition of the software system and the dependencies among the code entities. This technique uses a visual representation of an adjacency matrix to provide a scalable analysis tool. Advanced layout features such as an automatic level of detail algorithm and sorting strategies improve the readability of the visualization. Using a case study, we show how this technique can be applied in practice.